Clustering Algorithms Validated Using Relative Index Validation - Selvi, T. Senthil; Parimala, R (International Journal of Computer Sciences and Engineering, 2025)
Clustering pertains to the task of finding out groups of objects such that the objects of one group are dissimilar from other groups and is similar within the same group. This work uses feature selection technique like the Document frequency Feature selection (DFFS) and feature extraction techniques like Principal Component Analysis (PCA) and Kernel Principal Component Analysis (KPCA) were it constructs a small set of features from the original features. The newly constructed features run the K-Means algorithm without any loss of information. On several runs evaluate the accuracy for the clustering algorithms and record the results. For the obtained results, determine the cluster validation. Internal validation measures are employed to evaluate for cluster validation, based on these measures the relative validation measure is employed to determine the best clustering algorithm. Experiments are conducted for various benchmark datasets comprising of unlabelled documents and the final results prove to show that DFFS, KPCA followed by K-Means algorithm gives the best clustering results of accuracy